Central charge and universal combinations of amplitudes in two-dimensional theories away from criticality. - Cardy, J (1988)
For a general isotropic two-dimensional theory near criticality, the universal singular free energy per correlation volume fs2 is equal to -(c12)(2-)(1-)-1, where c is the central charge of the theory at criticality, is the usual specific-heat exponent, and is defined (for >0) in terms of the second moment of the energy correlations. Some generalizations of this result are also noted. © 1988 The American Physical Society.